Comunication Strategies Used By Billfath Speaking Class Students In Order To Deal With Their Speaking Preoblem - Rajid Khurniawan (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2020)
For some English students, speaking in English can be a big problem. Sometime the students do not know how to handle it. This research tried to investigate the communications strategies used by third semester English students of Billfath University in order to deal with their speaking problem. This research used descriptive qualitative to cultivate the data. The writer used communication strategies from Tarone’taxonomy as the theory. The writer took 15 students as the sample to be investigated. The writer used interview to take the data. The goal of this research is to investigate the kinds of communication strategies used by English speaking class in third semester. From this research we can see what is the most popular strategies used by students to solve students speaking problem and also we can see what is the most rarely strategies used by the students .Hopefully the result of this research can be a basic perspective to know any kinds of communication strategies used by the students so we can give better solution to the students in order to improve their speaking skill.